2020
DOI: 10.3844/sgamrsp.2020.24.40
|View full text |Cite
|
Sign up to set email alerts
|

Fire Resistance Testing of a Timber-Glass Composite Beam

Abstract: Glass structures have been increasingly utilised in modern construction for decades with load-bearing walls or facades as the most common elements. However, the use of glass beams has recently been given more attention but its application as load-bearing elements has been limited by the low tensile resistance, its brittle behaviour during failure and concerns of its performance in case of fire. Parts of these aspects can be covered by using Timber-Glass composites beams, with timber flanges and a glass web. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, there are still several open questions regarding the design of load-bearing glass. Among others, one of the challenging issues that will be partly addressed in this paper is related to the increased thermal exposure of glass in facades, and its effects on the mechanical properties of load-bearing glass systems [20][21][22][23].…”
Section: Of 24mentioning
confidence: 99%
“…However, there are still several open questions regarding the design of load-bearing glass. Among others, one of the challenging issues that will be partly addressed in this paper is related to the increased thermal exposure of glass in facades, and its effects on the mechanical properties of load-bearing glass systems [20][21][22][23].…”
Section: Of 24mentioning
confidence: 99%
“…The required surface film and surface radiation surface interactions able to account for the thermal exposure of glass and timber (for both the indoor and outdoor faces) were defined according to literature background for similar structural solutions Sjöström et al, 2020). Along the longitudinal and transversal mid-section of the so assembled FE models, finally, symmetry conditions were accounted to reproduce the thermal performance of 1/4th model as a part of the full-scale facade element.…”
Section: Component Assessmentmentioning
confidence: 99%
“…Even though several European standards apply to glass products (EN 12543-2; prEN 13474-2), an harmonized and exhaustive Eurocode for the load-bearing design of glass structures in Europe is still in preparation (Feldmann and Di Biase, 2018;CEN/TC 250, 2019a;2019b) and national guidelines for dimensioning or verification of glass elements are available (see for example (CNR-DT 210/2013;Buildings Department, 2018;Feldmann et al, 2014). Further open issues for the design of load-bearing glass elements are represented by elevated thermal exposures and related effects on the mechanical material properties (Bedon, 2017;Bedon and Louter, 2018;Kozlowski et al, 2018;Sjöström et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This operational condition is typical of horizontal building components in roofs or slabs (i.e., Figure 2) that are already designed with ordinary glass, but could be even subjected to a thermo-mechanical combination of actions. In this regard, few literature studies can be found about the mechanical behaviour and load-bearing capacity of structural glass components under combined fire and sustained out-of-plane loading [3,18,19]. This paper explores further the reliability of the available failure detection methods that are expected to support the required verifications, towards the definition of standardized procedures.…”
Section: Introductionmentioning
confidence: 99%